SOLUTION OF ENERGY RESOURCES SAVING TASKS BY REGULATION OF THE TEMPERATURE FIELD IN THE BAKERY CAMERA - G. V. Alexeev; A. P. Savelyev; N. E. Titova (Современная наука и инновации)
Global trends - priority directions of development of the food industry are resource saving and expansion of the range of the made food for fuller satisfaction of consumers.